Case report: A rare presentation of sigmoid volvulus during pregnancy with an integrative postoperative approach - Al-Sattam Zahraa Muhmmed Jameel; Mahdi Saleh Sabah; Alaa-Alden Fadhel Hussein (Scripta Medica)
Sigmoid volvulus during pregnancy is a rare but serious condition that can threaten the lives of both mother and baby. The estimated incidence is less than 1 in 10,000 pregnancies, with high maternal and foetal mortality rates if untreated. Predisposing factors include chronic constipation, previous abdominal surgeries and physiological changes such as reduced bowel motility due to elevated progesterone levels. A growing body of evidence suggests that integrative medicine approaches, including dietary fibre optimisation, probiotic supplementation and stress reduction techniques, may support bowel function and mitigate risk factors for volvulus. Here, a case of sigmoid volvulus in a 25-year-old pregnant woman at 34 weeks of gestation is presented, emphasising the importance of early diagnosis and a multidisciplinary approach, complemented by integrative strategies for postoperative care.